Digital surface model (DSM)copnstruction and flood hazard simulation for development plans in Naga City, Philippines - 414149 Muhammad Zulkarnin Abdul Rahman (Enschede : University Netherlands, 2006)
Thesis (Master of Science (Geo-Information Science and Earth Observation)) - University Netherlands, 2006